Disclosing Fiscal Risks in the Post-Crisis World. (IMF Staff Position Notes; Staff Position Note, 2009)
This paper discusses appropriate methods for disclosing fiscal risks from exogenous shocks and the realization of explicit or implicit contingent obligations of the government. Expanding on previous guidance prepared prior to the crisis, the note focuses on fiscal risks emerging from recent public interventions in the financial sector. Information on fiscal risks and its public reporting leads to a better understanding of the true state of the public finances. Thus, it helps policymakers design and gets public support for, appropriate responses to the realization of various contingencies. More specifically, in the context of the unfolding global financial crisis, a wide range of public sector interventions have been in support of the financial system. Although these interventions have been necessary, they have generated further fiscal risks. Comprehensive reporting would help governments to define a management strategy of the assets and liabilities that they have taken on their balance sheet and to prepare exit strategies for reducing their presence in the financial sector and eventually withdrawing support.